2010
DOI: 10.1021/jp103967x
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol-Derived Bimetallic Alloy Powders: Bridging the Gap

Abstract: We present aerosol-derived alloy powders as a uniquely useful platform for studying the contribution of the metal phase to multifunctional supported catalysts. Multimetallic heterogeneous catalysts made by traditional methods are usually nonhomogenous while UHV-based methods, such as mass selected clusters or metal vapor deposited on single crystals, lead to considerably more homogeneous, well-defined samples. However, these well-defined samples have low surface areas and do not lend themselves to catalytic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
44
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 51 publications
10
44
0
Order By: Relevance
“…In line with this finding, a recent study about the influence of ZnO facets on the performances of Pd/ZnO catalysts for MSR also reached the same conclusion [41,42]. Authors reported that at comparable Pd/ZnO catalyst composition, the polar sample was more selective than the nonpolar one due to the preferential formation of the PdZnl3 phase, which is selective toward CO2, on the polar ZnO [41,42]. From the results compiled in Tables 1 and 3, it can be inferred that the polarity ratio of ZnO support does not exert any promoting effect on activity but clearly affects the selectivity (Fig.…”
Section: Catalytic Activity Of Cuo/zno Samples In the Conventional Resupporting
confidence: 76%
See 1 more Smart Citation
“…In line with this finding, a recent study about the influence of ZnO facets on the performances of Pd/ZnO catalysts for MSR also reached the same conclusion [41,42]. Authors reported that at comparable Pd/ZnO catalyst composition, the polar sample was more selective than the nonpolar one due to the preferential formation of the PdZnl3 phase, which is selective toward CO2, on the polar ZnO [41,42]. From the results compiled in Tables 1 and 3, it can be inferred that the polarity ratio of ZnO support does not exert any promoting effect on activity but clearly affects the selectivity (Fig.…”
Section: Catalytic Activity Of Cuo/zno Samples In the Conventional Resupporting
confidence: 76%
“…ZnO was also found to affect the activity and selectivity of PdZnO catalysts in MSR reaction [32]. In line with this finding, a recent study about the influence of ZnO facets on the performances of Pd/ZnO catalysts for MSR also reached the same conclusion [41,42]. Authors reported that at comparable Pd/ZnO catalyst composition, the polar sample was more selective than the nonpolar one due to the preferential formation of the PdZnl3 phase, which is selective toward CO2, on the polar ZnO [41,42].…”
Section: Catalytic Activity Of Cuo/zno Samples In the Conventional Resupporting
confidence: 66%
“…This reversibility was confirmed by their Zn LMM Auger measurements by a shoulder at higher E kin in the reduced state, representing the intermetallic compound. More recent measurements confirmed the alloying process in aerosol-derived PdZn particles [16] (335 eV → 335.7 eV) and by monitoring the Zn3d peak [17]. A difference from metallic palladium (335 eV) to monolayer PdZn (335.3 eV) and multilayer PdZn (335.8 eV) has been reported by Rameshan et al [18].…”
Section: Xpsmentioning
confidence: 58%
“…In particular, the presence of well-dispersed ZnO domains on the support surface and/or as patches onto the PdZn bimetallic crystallites under MSR reaction condition, seems to be crucial for obtaining high turnover frequencies. Nonetheless, other authors have concluded that just the right PdZn alloy (namely, tetragonal PdZn␤ 1 ) suffices to grant high S CO2 and high TOF values [26], albeit under MSR conditions oxidized Zn species seem to be present in their pre-reduced bimetallic particles as was suggested by Lorenz et al [28] based on their relevant XPS spectra, probably because those alloy powders were again exposed to water.…”
Section: Discussionmentioning
confidence: 92%
“…This pretreatment was chosen to ensure the formation of a PdZn alloy (wherever applicable [7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]) prior to evaluating the catalysts' performance. The MSR study was done using 'temperature steps', from 398 to 623 K (1 h/ea.…”
Section: Catalysts Performance Experimentsmentioning
confidence: 99%